Kuasa dan Resistensi : Analisis Narasi “Panggil Aku Kartini Saja” Karya Pramoedya Ananta Toer dalam Perspektif Foucault - Najwa Fitri Sahira; Nehemia Diah K Sianturi; Riva Amanda (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This article analyzes the narrative of Pramoedya Ananta Toer's novel Panggil Aku Kartini Saja from the perspective of Michel Foucault's theory of power and resistance. This study aims to understand how power relations operate in the text and how Kartini as the main character shows a form of resistance to the patriarchal and colonial systems. With a qualitative descriptive approach, this study highlights two main aspects in the novel: first, how feudal and colonial powers form norms that limit women, and second, how Kartini carries out resistance through thinking, writing, and establishing schools for women. The research findings show that Kartini is not only an object of power, but also an active subject in fighting the oppressive system. This novel represents the struggle of women in negotiating their identity and space in a society dominated by colonial and patriarchal powers. Thus, the narrative of Panggil Aku Kartini Saja can be understood as a form of counter-discourse that criticizes the existing power structure.